2017
DOI: 10.1007/s11926-017-0629-9
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers for Musculoskeletal Pain Conditions: Use of Brain Imaging and Machine Learning

Abstract: Chronic musculoskeletal pain condition often shows poor correlations between tissue abnormalities and clinical pain. Therefore, classification of pain conditions like chronic low back pain, osteoarthritis, and fibromyalgia depends mostly on self report and less on objective findings like X-ray or magnetic resonance imaging (MRI) changes. However, recent advances in structural and functional brain imaging have identified brain abnormalities in chronic pain conditions that can be used for illness classification.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(34 citation statements)
references
References 57 publications
0
33
0
1
Order By: Relevance
“…The characteristics of white matter (axonal integrity) or gray matter (integrity of neuronal bodies) are related to the structural characteristics of the brain assessed through fMRI [255]. Using this technique as a basis, alterations in white matter have been related to different chronic pain conditions [256,257].…”
Section: Functional Magnetic Resonance Imaging (Fmri) and Chronic Painmentioning
confidence: 99%
See 1 more Smart Citation
“…The characteristics of white matter (axonal integrity) or gray matter (integrity of neuronal bodies) are related to the structural characteristics of the brain assessed through fMRI [255]. Using this technique as a basis, alterations in white matter have been related to different chronic pain conditions [256,257].…”
Section: Functional Magnetic Resonance Imaging (Fmri) and Chronic Painmentioning
confidence: 99%
“…As the evaluation of chronic pain is a complex task that often poses a challenge due to the amount of data to be managed, especially in the case of facial expression images, MRI, and multisensory approaches combining different approaches described so far, in recent years numerous machine learning algorithms have been proposed [253,255,282]. In a generic way, pain assessment is usually performed through procedures in which the following main stages can be distinguished:…”
Section: Processing Algorithms and Computational Models For Pain Assementioning
confidence: 99%
“…These physicians stated that Watson's recommendations were too narrowly focused on American studies and physician expertise, and failed to account for international knowledge and contexts [50]. The distrust amongst HCPs was also raised with regards to machine learning programs being difficult to both understand and explain [51,52]. In contrast, a fear exists that some HCPs may place too much faith in the outputs of machine learning processes, even if the resulting reports, such as brain mapping results from AI systems, are inconclusive [47].…”
Section: Trust In Ai Applicationsmentioning
confidence: 99%
“…Illustrated in the literature reviewed were overarching ethical concerns about privacy, trust, accountability, and bias, each of which were both interdependent and mutually reinforcing. Accountability, for instance, was a noted concern when considering who ought to bear responsibility for AI errors in patient diagnoses [51,56,57], while also a recognized issue in protecting patient privacy within data sharing partnerships [2]. The security of confidential patient data, in turn, was identified as critical for eliciting patient trust in the use of AI technology for health [45].…”
Section: Cross-cutting Themes and Asymmetriesmentioning
confidence: 99%
“…Interestingly, a "multisensory" classifier, which was trained on non-painful stimulation, showed increased responses of the insula/operculum, posterior cingulate, and medial prefrontal regions and reduced responses of the primary and secondary sensory cortices, basal ganglia, and cerebellum [28]. Similarly, Boissoneault J et al [29] described classification ML techniques which are capable of separating MRI-based brain biomarkers of chronic pain patients from healthy controls with high accuracy. Finally, Sevel et al [30] used ML to compare the performance of structural MRI data and self-reported measures for distinguishing healthy from FM and CHS patients.…”
Section: Highlight By Milos Ljubisavljevicmentioning
confidence: 99%